Reliability of kinematics and kinetics associated with horizontal single leg drop jump assessment. A brief report - Stalbom, M.; Jonsson Holm, D.; Cronin, J. B.; Keogh, J. W. L. (Journal of Sports Science & Medicine, 2007)
Determining the reliability of a unilateral horizontal drop jump for displacement provided the focus for this research. Eighteen male subjects were required to step off a 20cm box and land on a force plate with one leg and thereafter jump for maximal horizontal displacement on two different days. Dependent variables from the jump assessment included mean and peak vertical (V) and horizontal (H) ground reaction forces (GRF) and impulses, horizontal displacement and contact time. The between-trial variability of all kinematic and kinetic measures was less than 7%. The most consistent measure over both trials was the horizontal displacement jumped (1.2 to 1.4%) and the most variable were the contact time the first day (6.5%) and peak HGRF the second day (4.3%). In all cases there was less variation associated with the second rather than the first day. In terms of test-retest variability the percent changes in the means and coefficient of variations (CVs) were all under 10%. The smallest changes in the mean (0.43 %), least variation (< 2.26 %) and second highest intraclass correlation co-efficient (ICC = 0.95) were found for horizontal displacement jumped. The highest ICC (0.96) was found for horizontal impulse. Given the reliability of the single leg drop jump, it may offer better prognostic and diagnostic information than that obtained with bilateral vertical jumps.